Sequencing Analysis and Identification of the Primary Peptide Component of the Dialyzable Leukocyte Extract “Transferon Oral”: The Starting Point to Understand Its Mechanism of Action - Vallejo-Castillo, Luis; Favari, Liliana; Vázquez-Leyva, Said; Mellado-Sánchez, Gabriela; Macías-Palacios, Zaira; López-Juárez, Leonardo E.; Valencia-Flores, Luis; Medina-Rivero, Emilio; Chacón-Salinas, Rommel; Pavón, Lenin; Pérez-Tapia, Sonia Mayra (Frontiers in Pharmacology, 2020)
“Transferon Oral” is a peptide-derived product with immunomodulatory properties obtained from the lysis and dialysis of human buffy coat. Its active pharmaceutical ingredient, generically known as Dialyzable Leucocyte Extract, is a mixture of peptide populations with reproducible proportions among batches. “Transferon Oral” modulates IFN-γ, TNF-α, and IL-6 and increases the survival rate in a herpes infection murine model when oropharyngeally (ORO) administered, which correlate with clinical observations where “Transferon Oral” is used as a therapeutic auxiliary in inflammatory diseases. Notwithstanding, how a peptide-derived product elicits systemic modulation of cytokines when ORO administered remains unclear. To shed light on the pharmacology of “Transferon Oral” its peptide components must be known. Ten “Transferon Oral” batches were sequenced by mass spectrometry and the intact peptides were identified. The most abundant peptides were the monomeric human Ubiquitin (Ub), a globular low-molecular weight protein, and a Ub variant which lacks the two-terminal Gly (Ub-GG). Recombinant Ub prevented murine death when ORO administered in a herpes infection murine model. Besides, the percentage of survival increased in groups treated with Transferon Oral+Ub and decreased in groups treated with Ub-depleted “Transferon Oral” respect to the group treated with “Transferon Oral” only. Our findings indicate that the biological properties of “Transferon Oral” are partially associated to the Ub content, which may activate its extracellular receptor (CXCR-4) in the stomach eliciting systemic immunomodulatory effects via vagus nerve. This is the first report that identifies an active component of “Transferon Oral” with the potential for the development of oral peptide immunomodulators.